Phytodiversity and Ethnobotanical Features of Plants of Shahbaz Garhi Mardan, Khyber Pakhtunkhwa, Pakistan - Parveen, Sadia; Badshah, Lal; Ullah, Asad; Ali, Syed Ghias; Shah, Syed Mukaram; Ali, Usman; Zaman, Akhtar; Siddiqui, Sara Hamid (Ethnobotany Research and Applications, 2021)
Background: Plants provide food, clothing, shelter, medicines, fodder, fuel wood and ecosystem services. The floristic diversity of any area plays an important role in the sustainable livelihood and food security of the inhabitants of that area. The people of the research area Shahbaz Garhi, District Mardan are living in the far flung and backward area. They are dependent on plants and plants products for supporting their livelihood and other needs. They obtain food, fuel, timber, medicines and fodder from plants and also use plants for ornamental purposes. Since the area has a rich flora which was not previously documented. Similarly, the inhabitants use these plants for many purposes. Therefore, the present study was planned to document the flora and its local uses and to know how the local people use these plant natural resources to support their livelihood. Methods: Thorough collection of plants was made from the research area during 2019-2020. Plants were collected and the related data was documented on the spot in the field. Identification was carried out with the help of authentic literature. The ethnobotanical data was collected through questionnaires and 50 informants were interviewed, whose age was ranging from 20-60 years. Standard procedures were adopted for ethnobotanical information collection which includes (Stijfhoorn 1996-1997) and (Martin 2004) procedures and further data authentication was made by adopting artifact (ex-situ) and inventory (in-situ) methods. Results: A total of 85 species belonging to 42 families were recorded. Out of 42 families, 35 families were dicots, 5 were monocots and 2 families were gymnosperms. The dominant family was Asteraceae comprised of 7 genera (9.09 %) and 7 species (8.23 %) followed by Poaceae, Fabaceae and Amaranthaceae with 5 species each, while Cupressaceae, Myrtaceae, Oleaceae, Rhamnaceae, Salicaceae, Solanaceae and Verbenaceae with 3 species each and the remaining families were represented by 2 or less species. The life form class was dominated by Therophytes comprised of 31 spp. (36.4%) followed by Nanophanerophytes 24 spp. (28.2 %) and Chamaephytes 11 spp. (12.9 %). The leaf size spectra showed that Microphylls was dominant with 25 spp. (29.4 %), followed by Mesophylls with 24 spp. (28.2 %), while the Nanophylls with 12 spp. (14.1%) and Leptophylls with 10 spp. (11.7 %). The habit of plants showed that 43 species (50.5 %) were herbs, 28 species (32.5 %) were trees, and 14 spp. (16.4 %) were shrubs. The ethnobotanical analysis of 58 spp. showed that medicinal plants were dominant with 44 spp. (75.8%) followed by fodder 27 spp. (46.5 %), fuel wood 21 spp. (36.2 %), ornamental 15 spp. (27.5 %), food 13 spp. (22.4 %) and timber 11 spp. (18.9 %). All the 85 species were evaluated for conservation status. During the conservation status studies it was found that 1 species (1.17 %) i.e., Ailanthus altissima was endangered, 12 species (14.1 %) were least concern, and 72 (84.7 %) species were not Eealuated. The indigenous species were 34 (40%) and introduced were 51 (60%). Among the total species impacts of 51 introduced species were studied, in which most species were noted for interfering local flora 28 (54.90%),9 (17.64%) for replacing local flora, 6 (11.76%) as weeds /interfering crops, 2 (3.92%) were allelopathic and 6 (11.76%) were without any impacts. Conclusion: It was revealed during the present study that the area has a rich diversity of plants and the people of the area use these plants for medicinal, fodder, fuel wood, ornamental, food, and timber purposes. The people of the area use these plants and their products to support their livelihood and other needs. Keywords: Phytodiversity, ethnobotanical features, Shahbaz Garhi, Mardan, Pakistan.